Effects of C/N ratios on the oxidation resistance of SiCN fibers in air. (15th April 2021) - Long, Xin; Shao, Changwei; Zhang, Shuai; Wang, Yingde
Highlights: The oxidation of SiCN fibers is a diffusion-controlled process that obey the parabolic oxidation law. SiCN fibers with lower C/N ratios present rather lower oxidation rate constant but show larger tensile strength decrement. The formation of rough oxidation layer mainly caused the tensile strength decrement of SiCN fibers with lower C/N ratios. Abstract: In this work, the high-temperature oxidation behavior of SiCN fibers with different C/N ratios in air was researched in detail. The SiCN fibers showed a diffusion-controlled oxidation process that obeys the parabolic oxidation law, with the oxidation rate decreased as the C/N ratios decreasing. Although SiCN fibers with lower C/N ratios presented rather lower oxidation rate, they showed a larger tensile strength decrement after oxidizing at high temperatures. This phenomenon was contributed to the enhanced stress concentration by the formation of rough interface between fiber interior and oxidation layer.